1987
DOI: 10.1017/s003382220004371x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Implications of Chenier Dates in Northern Australia

Abstract: The characterization of late Holocene climates in northern Australia has, in the past, been based on local investigations. This examination of the chenier record of northern Australia indicates that there has been a statistically significant regional change in conditions between 1600–2800 years bp, possibly a period of relative aridity. Support for this conclusion may be found in the vegetation record from the Atherton Tableland where numerical comparisons of dryland fossil and modern pollen spectra suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…On the Groote Eylandt archipelago, effective precipitation declined sharply soon after 3700 BP, with evidence across Australia indicating that climate became more variable after this time (Shulmeister and Lees 1995). Geomorphic data based on the dating of cheniers and on sediment and pollen records from cheniers and coastal dunefields (Clarke et al 1979;Lees 1992b;Lees and Clements 1987;Lees et al 1990Lees et al , 1992Shulmeister 1992;Shulmeister and Lees 1992) indicates that some of the observed changes in these systems are synchronous across north Australia, and may represent coherent, broad-scale climatic signals (Prebble et al 2005:367-9;Shulmeister 1999:82).…”
Section: Holocene Patterns Of Climatic and Environmental Changementioning
confidence: 99%
“…On the Groote Eylandt archipelago, effective precipitation declined sharply soon after 3700 BP, with evidence across Australia indicating that climate became more variable after this time (Shulmeister and Lees 1995). Geomorphic data based on the dating of cheniers and on sediment and pollen records from cheniers and coastal dunefields (Clarke et al 1979;Lees 1992b;Lees and Clements 1987;Lees et al 1990Lees et al , 1992Shulmeister 1992;Shulmeister and Lees 1992) indicates that some of the observed changes in these systems are synchronous across north Australia, and may represent coherent, broad-scale climatic signals (Prebble et al 2005:367-9;Shulmeister 1999:82).…”
Section: Holocene Patterns Of Climatic and Environmental Changementioning
confidence: 99%
“…Other authors in this general region of northern Australia, particularly in the monsoonal zone, have interpreted geomorphic and stratigraphic evidence of cheniers, dunes and mangrove deposits as evidence of climate changes during the mid-late Holocene (Jennings, 1975;Semeniuk, 1981;Lees and Clements, 1987;Wasson and Donnelly, 1991;Lees, 1992). One pattern inferred for this region is that the climate has tended towards arid during the later Holocene (Jennings, 1975;Semeniuk, 1981).…”
Section: Discussionmentioning
confidence: 88%
“…Dates for the onset of mound-building from five major mound sites across northern Australia cluster between 1100 and 1800 years BP, indicating that this was a period of increased Orange-footed Scrubfowl activity (Stone 1989). From analysis of beach ridge and mud flat sequences along the northern Australian coastline, Lees & Clements (1987) have proposed that this period was also one of increased wet season rainfall. There appears to be a connection between these two events, suggesting that Orange-footed Scrubfowl numbers are prone to abundance under moister climatic conditions.…”
Section: Tim Stonementioning
confidence: 99%